Spring mass characteristics of the fastest men on earth - Taylor, M. J. D.; Beneke, R. (International Journal of Sports Medicine, 2012)
The spring mass model has widely been used to characterize the whole body during running and sprinting. However the spring mass characteristics of the world's fastest men are still unknown. Thus the aim of this study was to model these characteristics for currently the 3 fastest men on earth (Usain Bolt, Tyson Gay and Asafa Powell). This was done by using data collected during the 2009 World championships in Berlin and the modelling method of Morin et al. [21]. Even though Bolt achieved the greatest velocity (12.3 m.s - 1) over the 60-80 m split compared to his competitors, his estimated vertical stiffness (355.8 kN.m - 1) and leg stiffness (21.0 kN.m - 1) were significantly lower than his competitors. This reduction in stiffness is a consequence of Bolt's longer contact time (0.091 s) and lower step frequency (4.49 Hz). Thus Bolt is able to run at a greater velocity but with lower stiffness compared to his competitors.